2022
DOI: 10.1108/sampj-06-2021-0191
|View full text |Cite
|
Sign up to set email alerts
|

A natural capital accounting framework to communicate the environmental credentials of individual wool-producing businesses

Abstract: Purpose This paper aims to demonstrate methods that sustainability-conscious brands can use to include their primary producers in the measurement and reporting of the environment and sustainability performance of their supply chains. It explores three questions: How can farm businesses provide information required in sustainability reporting? What are the challenges and opportunities experienced in preparing and presenting the information? What future research and policy instruments might be needed to resolve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A world-class luxury fashion group, Kering Group and its brands (Gucci, Balenciaga, Bottega Veneta, Alexander McQueen and Kering Eyewear) are used to explain the findings of this study and to illustrate how the 12 innovative ideas for a sustainable fashion supply chain are put into practice. Kering Group is one of the leading international players committed to sustainability, innovation and environmental protection (Bai et al , 2022; Bertrand, 2021; Bull et al , 2022; Kelleci, 2022; Ogilvy e t al ., 2022). Kering Group owns luxury fashion brands including Gucci, Saint Laurent, Bottega Veneta, Balenciaga, Alexander McQueen, Brioni, Boucheron, Pomellato, DoDo, Qeelin and Kering Eyewear.…”
Section: Resultsmentioning
confidence: 99%
“…A world-class luxury fashion group, Kering Group and its brands (Gucci, Balenciaga, Bottega Veneta, Alexander McQueen and Kering Eyewear) are used to explain the findings of this study and to illustrate how the 12 innovative ideas for a sustainable fashion supply chain are put into practice. Kering Group is one of the leading international players committed to sustainability, innovation and environmental protection (Bai et al , 2022; Bertrand, 2021; Bull et al , 2022; Kelleci, 2022; Ogilvy e t al ., 2022). Kering Group owns luxury fashion brands including Gucci, Saint Laurent, Bottega Veneta, Balenciaga, Alexander McQueen, Brioni, Boucheron, Pomellato, DoDo, Qeelin and Kering Eyewear.…”
Section: Resultsmentioning
confidence: 99%
“…By collecting information on the financial status of the chemical industry for empirical research, it was found that the Development Capacity and debt level were both negatively related to the level of CAID; and positively related to the Company Scale [36]. An empirical analysis of the social responsibility reports of listed companies in the heavy pollution industry was conducted, and it was concluded that the Company Scale, Sustainability and Development Capacity are directly related to the level of information disclosure of the company [37].…”
Section: Carbon Accounting Information Disclosure Sustainability and ...mentioning
confidence: 99%
“…The modelled sequestration rates were used in combination with the ecologist's assessment of whether an EA was regenerating, stable or degrading, to estimate carbon gain (or loss) in each EA. Modelled sequestration rates for a given STM category varied from farm to farm because the FullCAM modelling takes into account localised factors such as rainfall, elevation and the productive potential for tree growth in that locale (details of the method including FullCAM parameters are described in Ogilvy et al (2022).…”
Section: The Processmentioning
confidence: 99%